2017
DOI: 10.1002/2016jd026416
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Patterns of Dry Deposition at a High‐Elevation Site in the Colorado Rocky Mountains

Abstract: In the Colorado Rocky Mountains, high‐elevation barren soils are deficient in carbon (C) and phosphorus (P) and enriched in nitrogen (N). The seasonal variability of dry deposition and its contributions to alpine elemental budgets is critical to understanding how dry deposition influences biogeochemical cycling in high‐elevation environments. In this 2 year study, we evaluated dry and wet deposition inputs to the Niwot Ridge Long Term Ecological Research (NWT LTER) site in the Colorado Rocky Mountains. The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 63 publications
(114 reference statements)
5
16
0
Order By: Relevance
“…Similar seasonal trends of total dissolved nitrogen and dissolved phosphorus in wet deposition have been observed by Mladenov et al 1. and Oldani10 at the same sampling site. The sample collected during 16–30 November 2010 has the highest concentration of TSP (Supplementary Table S1) and much lower mean and median OC and WSOC concentrations than the other samples, suggesting a contribution from dust enriched with inorganics.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar seasonal trends of total dissolved nitrogen and dissolved phosphorus in wet deposition have been observed by Mladenov et al 1. and Oldani10 at the same sampling site. The sample collected during 16–30 November 2010 has the highest concentration of TSP (Supplementary Table S1) and much lower mean and median OC and WSOC concentrations than the other samples, suggesting a contribution from dust enriched with inorganics.…”
Section: Discussionsupporting
confidence: 88%
“…Inputs of organic carbon, in particular, can influence redox reactions in the water column and sediments and can fuel microbial activity resulting in unanticipated consequences for otherwise isolated waters that we regard as our pristine reference sites. For the Rocky Mountains, studies have shown that the organic carbon load in atmospheric deposition is substantial110, but direct evidence of the sources of organic aerosols is thus far lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When discounting the site influenced by construction (Skywatch) and the spring season influenced by pollen deposition, our dust fluxes align with the most recent global compilation of direct dust flux observations, which reports the expected range for sites 10-1,000 km from secondary dust source at 1.0-20 g m −2 yr −1 (Lawrence & Neff, 2009). In addition, the fluxes measured at our alpine, subalpine, and montane sites are within the range reported by other atmospheric deposition studies in the Colorado Front Range (Liptzin & Seastedt, 2009;Oldani et al, 2017) and elsewhere in the Rocky Mountain West (Brahney et al, 2014;Dahms & Rawlins, 1996;Lawrence et al, 2010;Munroe et al, 2019). However, the dust fluxes we measured at lower elevations are some of the highest fluxes reported for the Rocky Mountains, even discounting fluxes measured at Skywatch and during the spring season ( Figure 6).…”
Section: Dust Fluxessupporting
confidence: 90%
“…If this is the case, the summertime elevation trend in mass fluxes described above may not extend to spring or annual mass fluxes. On the other hand, high-elevation sites may experience peak dust deposition during summer months, as was the case for a subalpine site on Niwot Ridge during 2013 (Oldani et al, 2017). The springtime delivery of dust to the Front Range may vary greatly from year to year, due to variability in dust storm transport path (Reynolds et al, 2016), whereas the summertime increase in dust deposition due to local anthropogenic sources may have lower interannual variability.…”
Section: 1029/2019jf005436mentioning
confidence: 99%